The effects of different levels of Aloe vera extract on some of the hematological and non-specific immune parameters in Siberian sturgeon (Acipenser baerii) - Bazari Moghaddam, S.; Haghighi, M.; Sharif Rohani, M.; Hamidi, M.; Ghasemi, M. (2017)
In this study, Aloe vera extract was used to evaluate its effects on hematological and immune parameters of Siberian sturgeon (Acipenser baerii). A total of 360 Siberian sturgeon weighing on average 10.95±0.04 g were randomly distributed in four treatments including a control group and three experimental groups (each with three replications). A. vera extract powder at the rate of 0.5%, 1% and 1.5% were added to the food. The fish were fed for 60 days in fiberglass tanks. At the end of the first and second months of breeding, the necessary samplings for hematological studies were done. The physicochemical parameters of water were recorded every day. The results showed significant differences (p<0.05) in the amount of RBC, hemoglobin, MCV, WBC, lysozyme and ACH50 in the treatments compared to the control group at the end of the breeding period. The results showed that A. vera extract has the effect of a non-specific immune system booster and using the extract in particular at the level of 1.5% as an immune stimulant in the diet of Siberian sturgeon can be effective in preventing disease in this species. Published